FACTORS AFFECTING INFANT MORTALITY RATE IN KARANGASEM, BALI - Ni Luh Putu Suciptawati; Ni Luh Putu Suciptawati; Made Asih; Kartika Sari; I G A M Srinadi (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2019)
The purpose of this study was to determine the factors that influence the infant mortality rate in Karangasem, Bali. The method used in this research is the Log Linier model. In the Log linear model analyze relationship pattern among group of categorical variables which include an association of two or more variables, either simultaneously or partially. A Patterned relationship between variables can be seen from the interaction between variables. Log linear analysis does not distinguish between explanatory variables and response variables. The population in this study was all babies born in Karangasem in 2015 that is as many as 7,895 babies with live birth status and as many as 7,835 babies and 60 infants died. As a sample, 100 babies were taken, of which 60 were live and 40 died. The results show that infant mortality is affected by infant weight, how old the mother during childbirth, and interaction between birth spacing and infant weight